2017
DOI: 10.1097/meg.0000000000000967
|View full text |Cite
|
Sign up to set email alerts
|

Long-term rifaximin therapy as a primary prevention of hepatorenal syndrome

Abstract: Rifaximin may be useful as a primary prevention of HRS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…Another retrospective study examining 145 patients with cirrhosis showed rifaximin treatment was significantly associated with prolonged overall survival and reduced risks of spontaneous bacterial peritonitis, variceal bleeding and recurrent HE . A further randomised study of rifaximin vs placebo also showed that rifaximin prevented the development of hepatorenal syndrome which in many cases develops in association with spontaneous bacterial peritonitis . Our cohort of transplant‐listed patients with decompensated cirrhosis corroborates these findings with an associated reduction in hospital readmission with complications of ascites, including spontaneous bacterial peritonitis and hepatorenal syndrome independently associated with rifaximin use.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Another retrospective study examining 145 patients with cirrhosis showed rifaximin treatment was significantly associated with prolonged overall survival and reduced risks of spontaneous bacterial peritonitis, variceal bleeding and recurrent HE . A further randomised study of rifaximin vs placebo also showed that rifaximin prevented the development of hepatorenal syndrome which in many cases develops in association with spontaneous bacterial peritonitis . Our cohort of transplant‐listed patients with decompensated cirrhosis corroborates these findings with an associated reduction in hospital readmission with complications of ascites, including spontaneous bacterial peritonitis and hepatorenal syndrome independently associated with rifaximin use.…”
Section: Discussionsupporting
confidence: 80%
“…28 A further randomised study of rifaximin vs placebo also showed that rifaximin prevented the development of hepatorenal syndrome which in many cases develops in association with spontaneous bacterial peritonitis. 29 Our cohort of transplant-listed patients with decompensated cirrhosis corroborates these findings with an associated reduction in hospital readmission with complications of ascites, including spontaneous bacterial peritonitis and hepatorenal syndrome independently associated with rifaximin use. Patients treated with rifaximin were less likely to require the need for prioritisation in this study and therefore this may have also had a bearing on any perceivable mortality difference.…”
Section: Quality Of Life In Patients With Cirrhosis and Overt He In Rsupporting
confidence: 80%
“…Hepatology and Gastroenterology Department, National Liver Institute, Menoufia University, Yassin Abdel-Ghafar street, Shebeen El-Kom, Menoufia 32511, Egypt. 2 Radiology Department, National Liver Institute, Menoufia University, Shebeen El-Kom, Egypt. 3 National Liver Institute, Menoufia University, Shebeen El-Kom, Egypt.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, TIPS was rapidly applied to the treatment of many of the complications of portal hypertension when the shunt could be placed with relative ease. These complications include active bleeding of gastro-esophageal varices, control of refractory cirrhotic ascites and hepatic hydrothorax, and treatment of hepatorenal failure and hepato-pulmonary syndrome [1,2]. Hepatic encephalopathy (HE) is a well-known complication of patients with liver cirrhosis after TIPS; its pathogenesis is not well understood [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…105 Rifaximin has been shown to reduce the incidence of HRS AKI, and additional studies have investigated the effect of administration to patients with cirrhosis and ascites, and these have shown that the overall blood urea nitrogen and serum creatinine concentrations were statistically significantly lower in the rifaximin group compared with the control group who received standard medical care. 106 Rifaximin also may decrease the plasma concentrations of interleukin 6, tumor necrosis factor-a, and endotoxins, which play a crucial role in the development of SBP and HRS AKI. 107…”
Section: Experimental Agentsmentioning
confidence: 99%